Factor structure and measurement invariance of the Brief Symptom Inventory (BSI-18) in cancer patients - Calderon, Caterina (Int J Clin Health Psychol, 2020)
Background/Objective: The purpose of this study was to assess psychometric properties of the Brief Symptom Inventory (BSI-18), evaluate the measurement invariance with respect to sex, age, and tumor location, and to analyze associations between social support and sociodemographic and clinical variables among individuals with resected, non-advanced cancer. Method: A confirmatory factor analysis was conducted to explore the dimensionality of the scale and test invariance across sex, age, and tumor localization in a prospective, multicenter cohort of 877 patients who completed the BSI-18 and Multidimensional Scale of Perceived Social Support (MSPSS). Results: The results show that 3-factor and 1-factor measurement models provided a good fit to the data; however, a three-factor, second-order model was deemed more appropriate and parsimonious in this population. Alpha coefficients ranged between .75 and .88. Test of measurement invariance showed strong invariance results for sex, age, and tumor location; strong invariance over time was likewise assumed. Less perceived social support appears to correlate with all BSI factors. Conclusions: The study confirmed the tridimensional structure of the BSI-18 and invariance across age, sex, and tumor localization. We recommend using this instrument to measure anxiety, depression, and somatization in epidemiological research and clinical practice.